Pengaruh Gaya Kepemimpinan, Disiplin Kerja Dan Motivasi Terhadap Produktivitas Pegawai Bagian Umum Balai Kota Malang - Fa’jiah, Cholifatul; Priyono, Achmad Agus; Saraswati, Ety (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to determine and analyze the influence of leadership style, work discipline and motivation on productivity in the general section of Malang City Hall. The type of research used is quantitative research. The sample in this research were ASN employees at the General Department of Malang City Hall, numbering 33 respondents. The data collection technique used was through distributing questionnaires. The analytical method used is multiple linear regression analysis. The results of this research show that leadership style, work discipline, and motivation have a positive and significant effect on leadership style on productivity.  Keywords: Leadership Style, Work Discipline, Motivation, Productivity.